2020
DOI: 10.1007/s12108-020-09440-6
|View full text |Cite
|
Sign up to set email alerts
|

International Representation in US Social-Science Journals

Abstract: In this paper we examine the publication of international articles in the two leading journals in sociology, the American Sociological Review and the American Journal of Sociology. The most prominent journals in several other social-science fields, namely economics, demography, political science and education, are included for purposes of comparison. "International" is defined alternatively with respect to topics and authors. The journal with the least representation of international topics is the American Edu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Scholars have repeatedly shown that knowledge, concepts and instruments produced in North America and Western Europe benefit from the dominant position in the social sciences (Beigel, 2014; Jacobs and Mizrachi, 2020; Krause, 2016). In the case of postsocialist societies in Central and Eastern Europe, this dominance is reinforced by both the legacy of the Cold War and the internal hierarchies of Europe, which have consistently construed Eastern Europe as subordinate and inferior to Western Europe (Koobak and Marling, 2014; Krivonos and Näre, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Scholars have repeatedly shown that knowledge, concepts and instruments produced in North America and Western Europe benefit from the dominant position in the social sciences (Beigel, 2014; Jacobs and Mizrachi, 2020; Krause, 2016). In the case of postsocialist societies in Central and Eastern Europe, this dominance is reinforced by both the legacy of the Cold War and the internal hierarchies of Europe, which have consistently construed Eastern Europe as subordinate and inferior to Western Europe (Koobak and Marling, 2014; Krivonos and Näre, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Connell, 2007; see also Sklair, 2013). But while empirical tests of the globalization of different aspect of publishing formats in sociology have seen the light of day (Beigel, 2014;Collyer, 2018;Jacobs & Mizrachi, 2020;Koch et al, 2020;Koch & Vanderstraeten, 2019;Vanderstraeten & Eykens, 2018), hitherto systematic sociological-historical reflections on the particulars of the debate on global sociology do not exist (see also Abbott, 2020). 1 The official histories of these associations focus for the largest part on their aims and social structures, not on the roles they actually play in the internationalization processes (see Platt, 1998;Rhoades, 1981;Schuerkens, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Even if incomplete, such an evidence base helps us to see where the gaps are. Finally, as other recent work has noted, the exclusion of international research from top journals may not only have deleterious effects on the discipline, but also on the career prospects of researchers who engage in international work (Jacobs and Mizrachi 2020). An understanding of the mechanisms that produce and enable epistemic parochialism therefore offers journal editors, funding and educational institutions, and researchers the tools to change the status quo and incorporate more diverse perspectives into the process of scientific knowledge production.…”
mentioning
confidence: 99%